Prediction of multiple sclerosis outcomes when switching to ocrelizumab. (May 2022) - Zhong, Michael; van der Walt, Anneke; Stankovich, Jim; Kalincik, Tomas; Buzzard, Katherine; Skibina, Olga; Boz, Cavit; Hodgkinson, Suzanne; Slee, Mark; Lechner-Scott, Jeannette; Macdonell, Richard; Prevost, Julie; et al.
Background: Increasingly, people with relapsing-remitting multiple sclerosis (RRMS) are switched to highly effective disease-modifying therapies (DMTs) such as ocrelizumab. Objective: To determine predictors of relapse and disability progression when switching from another DMT to ocrelizumab. Methods: Patients with RRMS who switched to ocrelizumab were identified from the MSBase Registry and grouped by prior disease-modifying therapy (pDMT; interferon-β/glatiramer acetate, dimethyl fumarate, teriflunomide, fingolimod or natalizumab) and washout duration (<1 month, 1–2 months or 2–6 months). Survival analyses including multivariable Cox proportional hazard regression models were used to identify predictors of on-ocrelizumab relapse within 1 year, and 6-month confirmed disability progression (CDP). Results: After adjustment, relapse hazard when switching from fingolimod was greater than other pDMTs, but only in the first 3 months of ocrelizumab therapy (hazard ratio (HR) = 3.98, 95% confidence interval (CI) = 1.57–11.11, p = 0.004). The adjusted hazard for CDP was significantly higher with longer washout (2–6 m compared to <1 m: HR = 9.57, 95% CI = 1.92–47.64, p = 0.006). Conclusion: The risk of disability worsening during switch to ocrelizumab is reduced by short treatment gaps. Patients who cease fingolimod are at heightened relapse risk in the first 3 months on ocrelizumab. Prospective evaluation of strategies such as washout reduction may help optimise this switch.